MODELING OF FRICTION IN COLD STRIP ROLLING UNDER HYDRODYNAMIC LUBRICATION - ., Qamaruddin (RESULTAN : Jurnal Kajian Teknologi, 2015)
A friction model with the help of ANSYS software is made for cold strip rolling under hydrodynamic lubrication. The finite element model is developed from a flow problem of non-Newtonian incompressible fluid. The result of solution is nodal velocities over the arc of contact and the friction (shear stress) model is determined using the formula developed by Saxena et.al. The friction model as a result of applying ANSYS software shows the same trend as the existing developed model